Climate change research at universities : addressing the mitigation and adaptation challenges - Leal Filho, Walter (Springer, 2017)
This unique book provides a multidisciplinary review of current, climate-change research projects at universities around the globe, offering perspectives from all of the natural and social sciences. Numerous universities worldwide pursue state-of-the-art research on climate change, focussing on mitigation of its effects as well as human adaptation to it. However, the 2015 Paris 21st Conference of the Parties of the United Nations Framework Convention on Climate Change (UNFCCC) (COP 21)" demonstrated that there is still much room for improvement in the role played by universities in international negotiations and decision-making on climate change. To date, few scientific meetings have provided multidisciplinary perspectives on climate change in which researchers across the natural and social sciences could come together to exchange research findings and discuss methods relating to climate change mitigation and adaption studies. As a result the published literature has also lacked a broad perspective. This book fills that gap and is of interest to all researchers and policy-makers concerned with global climate change regardless of their area of expertise.
Keywords: Climatic changes -- Research.; elektronické knihy; electronic books